Genome-Wide Identification, Characterization and Expression Analysis of Soybean CHYR Gene Family - Bowei Jia (MDPI AG, 2021)
The CHYR (CHY ZINC-FINGER AND RING FINGER PROTEIN) proteins have been functionally characterized in iron regulation and stress response in Arabidopsis, rice and Populus. However, their roles in soybean have not yet been systematically investigated. Here, in this study, 16 GmCHYR genes with conserved Zinc_ribbon, CHY zinc finger and Ring finger domains were obtained and divided into three groups. Moreover, additional 2–3 hemerythrin domains could be found in the N terminus of Group III. Phylogenetic and homology analysis of CHYRs in green plants indicated that three groups might originate from different ancestors. Expectedly, GmCHYR genes shared similar conserved domains/motifs distribution within the same group. Gene expression analysis uncovered their special expression patterns in different soybean tissues/organs and under various abiotic stresses. Group I and II members were mainly involved in salt and alkaline stresses. The expression of Group III members was induced/repressed by dehydration, salt and alkaline stresses, indicating their diverse roles in response to abiotic stress. In conclusion, our work will benefit for further revealing the biological roles of GmCHYRs.